Louise Erdrich: Tracks, The Last Report on the Miracles at Little No Horse, The Plague of Doves - Madsen, Deborah Lea (Continuum (London), 2011)
Louise Erdrich has shaped the possibilities for Native American, women's and popular fiction in the United States during the late twentieth century. Louise Erdrich collects new essays by noted scholars of Native American Literature on three important novels that chart the trajectory of Erdrich's novelistic career, Tracks (1988), The Last Report on the Miracles At Little No Horse (2001) and The Plague of Doves (2007). The book illuminates Erdrich's multiperspectival representation of Native American culture and history. Focusing on such topics as humor, religion, ethnicity, gender, race, sexuality, trauma, history, and narrative form, the essays collected here offer fresh readings of Erdrich's explorations of Native American identities through her innovative fictions.